Zero sum game - Huang, S. L. (Tor, 2018)
Cas Russell is good at math. Scary good. The vector calculus blazing through her head lets her smash through armed men twice her size and dodge every bullet in a gunfight, and she'll take any job for the right price. As far as Cas knows, she<U+2019>s the only person around with a superpower...until she discovers someone with a power even more dangerous than her own. Someone who can reach directly into people<U+2019>s minds and twist their brains into Moebius strips. Someone intent on becoming the world<U+2019>s puppet master. Cas should run, like she usually does, but for once she's involved. There<U+2019>s only one problem... She doesn<U+2019>t know which of her thoughts are her own anymore.